"It's not for fun anymore": perfomance of masculinity as a source of stress among professional soccer players in South Africa - De Abreu, Chantelle Silva (Department of Psychology, 2017)
Youth from lower socio-economic status communities have been reported to perceive involvement in sport, and the potential of a career therein, as important for social mobility and identity. Males from these communities have been reported to make more of an investment in sport since it is perceived as the main source of supporting a family, as well as establishing a sense of hegemonic masculinity, as other options are often limited. The research aims of this study were to determine the stressors that South African professional soccer players face, with a focus on how masculinity shapes their experience of stress. The study examined how the pursuit of hegemonic masculinity is played out amongst elite South African soccer players and how this influences the personal and professional stressors that players have to negotiate. Semi-structured interviews with ten male athletes aged between 21 and 33 years from a professional soccer club in Cape Town, South Africa were conducted. Thematic analysis, adopting the lens of masculinity theories, was used to identify themes that emerged from the data. Across the interviews what strongly emerged were the off-field performances of masculinity which indicated how gaining acceptance in professional soccer is performed through a lifestyle of consumer products, women, fame, alcohol and partying. The data indicated how soccer provides an alternative way of life to gangs and crime in which men can still attain masculinity. However, with the option of attaining masculinity through soccer, came its own set of challenges as participants indicated the disparity within a soccer player's identity between the fantasy and the reality of being a professional soccer player. In addition there were also challenges to the ability of participants to access on-field performances of masculinity. This study adds to the literature on stress amongst athletes by exploring how social identity, and particularly masculinity, mediates experiences of stress amongst professional soccer players. It highlights the opportunity and need for the development of appropriate player well-being programmes which can be used to support professional athletes.